2021
DOI: 10.4103/jgid.jgid_171_19
|View full text |Cite
|
Sign up to set email alerts
|

Gaps in the Care Cascade among Human Immunodeficiency Virus-Exposed Infants Born in 2017 in Mashonaland East Province of Zimbabwe

Abstract: Introduction: Prevention of mother-to-child transmission (PMTCT) is a key strategy for ending the human immunodeficiency virus (HIV) pandemic. Most studies have focused on the mothers' side of the PMTCT cascade or the rate of vertical HIV transmission. Information on child-focused cascade is limited. We aimed to evaluate HIV testing, antiretroviral therapy (ART), and cotrimoxazole prophylaxis uptake and associated factors among HIV-exposed infants (HEIs) born in 2017. Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…The studies published between January 2012 and March 2022 were carried out in a range of East African countries; namely, Burundi [ 57 ], Comoros [ 57 ], Ethiopia [ 25 , 45 , 57 74 ], Kenya [ 57 , 75 78 ], Malawi [ 25 , 45 , 57 74 , 79 ], Mozambique [ 57 , 76 78 , 80 ], Rwanda [ 57 ], South Sudan [ 81 ], Tanzania [ 82 , 83 ], Uganda [ 39 , 57 , 84 87 ], Zambia [ 57 , 88 90 ], and Zimbabwe [ 57 , 91 96 ]. Studies conducted among eligible pregnant/postpartum women, infants and service providers were included in the analysis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The studies published between January 2012 and March 2022 were carried out in a range of East African countries; namely, Burundi [ 57 ], Comoros [ 57 ], Ethiopia [ 25 , 45 , 57 74 ], Kenya [ 57 , 75 78 ], Malawi [ 25 , 45 , 57 74 , 79 ], Mozambique [ 57 , 76 78 , 80 ], Rwanda [ 57 ], South Sudan [ 81 ], Tanzania [ 82 , 83 ], Uganda [ 39 , 57 , 84 87 ], Zambia [ 57 , 88 90 ], and Zimbabwe [ 57 , 91 96 ]. Studies conducted among eligible pregnant/postpartum women, infants and service providers were included in the analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Community and health care factors : Six studies [ 25 , 57 , 58 , 63 , 66 , 103 ] showed the presence of an association between place residence and maternal HIV testing. However, two studies on maternal HIV testing [ 65 , 75 ] and three studies on EID [ 62 , 91 , 92 ] revealed the absence of statistical association with place of residence. Women who lived in a community where there was no/low stigmatized attitude toward people living with HIV/AIDS [ 25 , 58 ] were more likely to be HIV tested than those who lived in a community that stigmatized HIV-positive patients [ 63 , 75 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation